What factors govern the procurement and use of silcrete during the Stone Age of South Africa?. (October 2017) - Will, Manuel; Mackay, Alex
Abstract: Fluctuations in the frequency of silcrete in lithic assemblages have been an important focus of Stone Age research in southern Africa. Here, we review temporal and spatial variation in silcrete abundance during the LSA and MSA of southern Africa and discuss mechanisms that might drive the differential acquisition and treatment of this raw material. Previous research has proposed a variety of explanations that include non-behavioural factors (sea level changes, climatic and environmental driving forces) and various behavioural determinants that range from functional constraints and economic considerations to socio-cultural preferences. In order to test these explanations and provide a systematic spatio-temporal overview of silcrete use, we performed a meta-analysis by collecting a database on silcrete abundance from a total of 25 Stone Age sites that encompass > 200 assemblages. Quantitative statistical analyses of this database reveal significant variation in silcrete prevalence among and between sites. The main temporal trajectory conforms to a bimodal pattern that features peak frequencies in MIS 4 & 3 as well as MIS 1. The results also demonstrate a significant association between silcrete abundance and technocomplexes with particularly high values for the Howiesons Poort, "post-HP" and Wilton, but not the Still Bay. Silcrete abundance is significantly correlated with the production of tools in general, and the manufacture of microlithic or backed artefacts in particular, suggesting an influence of functional considerations and potentially cultural preferences. In contrast, we found little support for the dependence of silcrete use on purely economic grounds such as procurement costs or a strong impact of non-behavioural factors such as changes in sea level or environmental circumstances. By operating on a large spatio-temporal scale with aggregated data, the results of this study can help to embed the acquisition and treatment of silcrete by Stone Age people in a wider behavioural and evolutionary framework. Highlights: Systematic meta-analysis of silcrete use in the Stone Age of southern Africa Bimodal pattern of silcrete abundance through time with peaks in MIS 4&3 and MIS 1 Significant association between silcrete prevalence and technocomplexes Silcrete abundance influenced by functional considerations and cultural preferences Little support for dependence of silcrete use on purely economic grounds, changes in sea level or environment